Acute Care Surgery Service Is Essential During a Nonsurgical Catastrophic Event, the COVID-19 Pandemic. Issue 12 (December 2020) - Bugaev, Nikolay; Hojman, Horacio M.; Breeze, Janis L.; Nasraway, Stanley A.; Arabian, Sandra S.; Holewinski, Sharon; Johnson, Benjamin P.
Background: The role of an acute care surgery (ACS) service during the COVID-19 pandemic is not well established. Methods: A retrospective review of the ACS service performance in an urban tertiary academic medical center. The study was performed between January and May 2020. The demographics, clinical characteristics, and outcomes of patients treated by the ACS service 2 months prior to the COVID surge (pre-COVID group) and during the first 2 months of the COVID-19 pandemic (surge group) were compared. Results: Trauma and emergency general surgery volumes decreased during the surge by 38% and 57%, respectively; but there was a 64% increase in critically ill patients. The proportion of patients in the Department of Surgery treated by the ACS service increased from 40% pre-COVID to 67% during the surge. The ACS service performed 32% and 57% of all surgical cases in the Department of Surgery during the pre-COVID and surge periods, respectively. The ACS service managed 23% of all critically ill patients in the institution during the surge. Critically ill patients with and without confirmed COVID-19 infection treated by ACS and non-ACS intensive care units during the surge did not differ in demographics, indicators of clinical severity, or hospital mortality:13.4% vs. 13.5% ( P = .99) for all critically ill patients; and 13.9% vs. 27.4% ( P = .12) for COVID-19 critically ill patients. Conclusion: Acute care surgery is an "essential" service during the COVID-19 pandemic, capable of managing critically ill nonsurgical patients while maintaining the provision of trauma and emergent surgical services. Level of Evidence: III. Study Type: Therapeutic.